Weighted ergodic theorem for contractions of Orlicz-Kantorovich lattice L_M(N,m) - Mukhamedov, Farrukh; Ganiev, Inomjon (School of Mathematical Sciences, Universiti Sains Malaysia, 2015)
In the present paper we prove a Besicovich weighted ergodic theorem for positive contractions acting on Orlich-Kantorovich space. Our main tool is the use of methods of measurable bundles of Banach-Kantorovich lattices.